Technology of Development of Academic Mobility of Students of Higher Educational Institutions Based on an Innovative Approach - kizi, Mingbayeva Tursunoy Ismatilla (European Journal of Life Safety and Stability (2660-9630), 2023)
The article is devoted to the problems of development of academic mobility of university students in the context of the transition of Russian education to a multilevel system. The article reveals the features of the current state of development of higher professional education from the standpoint of the competence-based approach and the formation of foreign language competence of students.